Horizontal transmission of the ectoparasite Gyrodactylus arcuatus (Monogenea: Gyrodactylidae) to the next generation of the three-spined stickleback Gasterosteus aculeatus - Lumme, Jaakko; Zietara, Marek S (Folia parasitologica, 2018)
In the parthenogenetic monogeneans of the genus Gyrodactylus Nordmann, 1832, the genetic diversity within or between hosts is determined by the relative roles of lateral transmission and clonal propagation. Clonality and limited transmission lead to high-amplitude metapopulation dynamics and strong genetic drift. In Baltic populations of the three-spined stickleback Gasterosteus aculeatus Linnaeus, the local mitochondrial diversity of Gyrodactylus arcuatus Bychowsky, 1933 is very high, and spatial differentiation weak. To understand the transmission dynamics in a single location, the transmission of the parasite from adults to next generation sticklebacks was investigated in a northern Baltic brackish water location. By sequencing 777 nt of cox1, as many as 38 separate mitochondrial haplotypes were identified. In August, the intensity of gyrodactylid infection on adult hosts was high, the haplotype diversity (h) was extreme and differentiation between fish was negligible (total h = 0.926, mean h = 0.938). In October, only 46% of the juvenile sticklebacks carried G. arcuatus. The number of parasites per young fish followed a Poisson distribution 0.92 ± 1.04 (mean ± SD) on October 2, and was clearly overdispersed 2.38 ± 5.00 on October 25. The total haplotype diversity of parasites on juveniles was nearly as high as in adults (h = 0.916), but the mean per fish was only h = 0.364 (FST = 0.60), due to low intensity of infection and rapid clonal propagation of early arrivals. The initial first come first served advantage of the first gyrodactylid colonisers will be lost during the host adulthood via continuous transmission. Nesting and polygamy are suggested as factors maintaining the high genetic diversity of the parasite population. The transmission dynamics and, consequently, the population structure of Baltic G. arcuatus is fundamentally different from that of G. salaris Malmberg, 1957, on the Baltic salmon Salmo salar Linnaeus.
Keywords: Animals; Trematoda; Female; infekce červy třídy Trematoda; Electron Transport Complex IV; Helminth Proteins; parasite transition; Trematode Infections; ženské pohlaví; Finland; nemoci ryb; respirační komplex IV; Fish Diseases; Host-Parasite Interactions; interakce hostitele a parazita; mitochondriální proteiny; competition; clonal propagation; Male; Haplotypes; Smegmamorpha; proteiny červů; Mitochondrial Proteins; zvířata; haplotypy; mužské pohlaví; Finsko